2014
DOI: 10.1001/jamaneurol.2014.808
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antiepileptic Drug Combination Therapy for Partial-Onset Seizures Based on Mechanisms of Action

Abstract: IMPORTANCE To our knowledge, the current study is the first to describe antiepileptic drug (AED) combination therapy patterns according to their mechanism of action (MOA) in a real-world setting and to evaluate the differences in outcomes comparing different-MOA combination therapy with same-MOA combination therapy for patients with partial-onset seizure.OBJECTIVE To compare treatment persistence and health care use with AED combinations categorized by MOA in patients with partial-onset seizures. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 14 publications
3
89
0
4
Order By: Relevance
“…Clinical evidence indicates that some combinations of 2 or more AEDs are capable of suppressing seizures in epilepsy patients refractory to the standard monotherapy [3][4][5] . It has been documented that the 3-drug combination of carbamazepine (CBZ), primidone and topiramate (TPM) exerted a state of seizure-freedom in patients with refractory epilepsy [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence indicates that some combinations of 2 or more AEDs are capable of suppressing seizures in epilepsy patients refractory to the standard monotherapy [3][4][5] . It has been documented that the 3-drug combination of carbamazepine (CBZ), primidone and topiramate (TPM) exerted a state of seizure-freedom in patients with refractory epilepsy [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[36] Persistence reflects therapeutic benefits in relation to undesirable effects, and has been used as primary outcome in many clinical trials and observational studies. [310] It is also a primary outcome measure recommended by the Commission on Antiepileptic Drugs of the International League Against Epilepsy in evaluating AED effectiveness. [3,6,7] …”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have indicated that combining AEDs with different mechanisms of action may confer synergistic effects, particularly for combinations including ␣-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor antagonists (Jonker et al, 2007). In humans, evidence from observational studies has suggested synergistic efficacy when the sodium channel blocker (SCB) lamotrigine is combined with valproic acid (Brodie and Yuen, 1997;Pisani et al, 1999), and a retrospective review of a US healthcare claims database has suggested that combining AEDs with different mechanisms of action may offer improved effectiveness compared with combinations with the same mechanisms, as measured by prolonged treatment continuation and reduced risks for hospitalization and emergency department visits (Margolis et al, 2014). Other recent efforts to identify potentially beneficial AED combinations have utilized post hoc analyses of data from pivotal trials (Sake et al, 2010).…”
Section: Introductionmentioning
confidence: 99%